Identifying the root Causes of Students' Comprehension Problems in Narrative Reading in EFL Education - Veronika Angelina Tampubolon; Natalia Widya Pasca Tarigan; Wariyati Wariyati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the difficulties encountered by Grade 7 students at SMP Panca Budi Medan in understanding narrative texts in an English as a Foreign Language (EFL) classroom. Employing a qualitative case study approach, data were collected through classroom observations, student and teacher interviews, and document analysis. The findings reveal that students face various challenges, including limited vocabulary, lack of understanding of narrative text structure, difficulty in making inferences, and low motivation toward reading. These difficulties are influenced by both linguistic and non-linguistic factors, such as students’ limited exposure to English reading materials and the lack of effective reading strategies. The study highlights the need for more interactive and strategy-based teaching practices to improve students' reading comprehension skills. It also recommends increased support from schools and teachers in promoting reading habits and providing engaging narrative texts suited to students' language proficiency levels.